The expression of leptin in oral wound healing in diabetes mellitus: An experimental study - El-Deeb, Amal M; Fansa, Hoda A; Wahba, Omneya M (International Journal of Health Sciences, 2018)
Objective: The present work evaluated histologically and immunohistochemically, the expression of leptin during healing of the incisional oral mucosal wound in diabetic rats as compared to healthy rats. Methods: Twenty-four, adult male Sprague–Dawley rats weighing on average150-200 gm were allocated equally into two groups: Group I (Control) and Group II (diabetic). Diabetes was induced by a single intraperitoneal injection of Streptozotocin STZ dissolved in distilled water. Each animal received experimental incision in buccal mucosa and sutured, the specimens were collected from the buccal mucosa of each animal at intervals of 7, 14,21 days and routinely processed for H&E and immunohistochemical staining for leptin. All measurement data were calculated as mean ± standard deviation. Results: Leptin expression was observed in the epithelium and in the vascular endothelial cells in both groups. In both the control and diabetic groups, the expression of leptin was significantly increased with time, there was extreme highly significant increase in the control group than in diabetic group after 7, 14 and 21 days (p = 0.000). Conclusion: The results of the present study suggested that leptin may promote wound healing in rat’s normal oral mucosa more than in diabetic. Further studies are needed to clarify the exact molecular mechanisms of leptin’s effects on wound healing and to determine the usefulness of leptin as a treatment to promote wound healing in the oral mucosa in diabetic and non-diabetic patients.